Marine Renewable Energy Clustering in the Mediterranean Sea: The Case of PELAGOS Project - Soukissian, Takvor H.; Adamopoulos, Christos; Prospathopoulos, Aristides; Karathanasi, Flora; Stergiopoulou, Lydia (Frontiers in Energy Research, 2019)
The main ideas presented in this work are an outcome of the Interreg MED project PELAGOS (Promoting innovative nEtworks and cLusters for mArine renewable energy synerGies in Mediterranean cOasts and iSlands). Since Blue Energy development is at its very beginning in the Mediterranean Sea, the aim of the paper is to present and discuss in depth the key-issues for a Marine Renewable Energy (MRE) cluster development in the Mediterranean and reveal its necessity for the commercial and sustainable development of Blue Energy in the area. This cluster is expected to stimulate the relevant Blue Energy sectors under the perspective of smart and sustainable growth. A healthy cluster is based on an efficient cluster policy. The main policy constituents (innovation, legislation and financial frameworks) are discussed taking into account the interrelated characteristics that are expected to specify the commercial development of MRE in the area. Key issues that can contribute to the establishment and acceleration of deployment of the related technological innovation are identified, and existent hindrances and challenges encountered in MRE sector are determined. The importance of solid financing instruments and strong collaborations among interested stakeholders is also highlighted for the viability of the MRE cluster. Finally, as an example of the cluster activities at a national level, the Greek Hub for Blue Energy is introduced. In this respect, aspects in terms of its structure and the services provided to its members are analyzed.